Language, Social Conflict, and Their Implications for the World of Education: A Case Study in One Region of Indonesia - Wastawa, I Wayan; Sutriyanti, Ni Komang; Suwadnyana, I Wayan; Subawa, I Made Pasek; Suyono, Suyono; Widiani, Ni Komang (Universitas Negeri Makassar, 2024)
Acts of violence in a changing society, as occurred in Balinuraga Village, South Lampung Regency, have had a significant impact on national stability. Based on this, the aim of this research is to analyze communication of social conflict between ethnic Lampung and ethnic Balinese in Balinuraga village, Way Panji District, South Lampung Regency.This type of research is qualitative research. Based on the problem investigated, this research is classified as case research, to provide a detailed description of the sources of conflict, impacts and social conflict communication management that are unique to the case. Primary data was obtained from 15 key informants from several ethnicities across generations and religions. The methods used to collect data were participant observation, in-depth interviews, document study, and triangulation. The data collection instrument is a questionnaire sheet. The technique used to analyze data is qualitative descriptive analysis. Data analysis was carried out qualitatively interpretatively by applying conflict theory, conflict management, functional structural theory and communication theory. From the communication perspective, the current research found out that the source of social conflict between Balinese ethnic (Balinuraga) and Lampung ethnic (Agom Village) in 2012 in Way Panji District, was communication could be the source of conflict if communication is influenced by elements of group sentiment. This poor communication has an impact on social conflict in Balinuraga village. The government has handled the consequences of conflict through reconciliation; rehabilitation; and post-conflict reconstruction. Likewise, the people of Balinuraga have also handled conflict through ideological integration and social integration